2019
DOI: 10.3390/nu11102449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics on Oral Candidiasis: A Systematic Review and Meta-Analysis

Abstract: Oral candidiasis (OC) is an increasing health problem due to the introduction of new drugs, population aging, and increasing prevalence of chronic illness. This study systematically reviews the effects of the oral intake of probiotics, prebiotics, and synbiotics on Candida spp. counts (colony-forming units (CFU)/mL) in oral and palatal samples. A literature search was conducted. Twelve studies, eight randomized clinical trials (RCTs), and four pre-post studies, resulted as eligible for the meta-analysis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 75 publications
0
41
0
Order By: Relevance
“…Bacteria commensally living in the environment of the human organism developed the property of modulating the host’s immune response. They can influence the production of cytokines and antibodies and increase the pool of regulatory T lymphocytes [ 23 ]. Lactobacillus strains have the ability to induce cytokine synthesis by the inflammatory cells.…”
Section: The Mechanism Of Action Of Probiotics In the Oral Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria commensally living in the environment of the human organism developed the property of modulating the host’s immune response. They can influence the production of cytokines and antibodies and increase the pool of regulatory T lymphocytes [ 23 ]. Lactobacillus strains have the ability to induce cytokine synthesis by the inflammatory cells.…”
Section: The Mechanism Of Action Of Probiotics In the Oral Cavitymentioning
confidence: 99%
“…This study systematically reviewed the effects of the intake of probiotics on oral candidiasis and concluded that this treatment had a beneficial effect on reducing oral Candida spp. counts [ 23 ].…”
Section: Probiotics and Oral Candidiasismentioning
confidence: 99%
“…Postbiotic supplementation derived from Lactobacillus paracasei was able to protect G. mellonella infected with C. auris and immunomodulate indicating a dual role in modulating host immune response [ 129 ]. Even meta-analysis is among the first study of such kind which establishes the effect of probiotics on oral candidiasis [ 130 ].…”
Section: Targeted Microbial Therapymentioning
confidence: 99%
“…S.mutans is the most common organism that leads to the development of caries (nikawa et al, 2004;Beighton, 2005). S.mutans is an acidogenic bacteria and it rapidly metabolizes carbohydrates resulting in lowering of ph in the oral cavity that leads to disturbance in hemostasis in the oral microbial community (hedberg et al, 2008).…”
Section: Role Of Probiotics In Oral Healthmentioning
confidence: 99%
“…(Seminario-Amez et al, 2017). hu et al and Mundula et al, studied that the probiotics had a favourable effect in treating oral candidiasis(hu et al, 2019) (Mundula et al, 2019).…”
Section: Name Of the Commercial Productmentioning
confidence: 99%